Identification of microplastics in the sediments of southern coasts of the Caspian Sea, north of Iran. (March 2020) - Mehdinia, Ali; Dehbandi, Reza; Hamzehpour, Ali; Rahnama, Reza
Abstract: Microplastic (MPs) pollution in the aquatic and terrestrial environments has caught many attentions in the scientific literatures. Currently, no information is available about MPs pollution in Caspian Sea, the largest lake in the world. This study indicates the first report on the MPs pollution in the sediments of the southern Caspian coastal zones, northern Iran. Density separation method was conducted on 17 surficial sediments. The combination of observation techniques including SEM-EDS analysis, polarized light microscopy and Raman micro-spectroscopy were used to identify MPs. The abundance and size of microplastics in the samples ranged between 25 and 330 items/kg and 250–500 μm, respectively. Fibers constituted the most common MPs shape and polystyrene (PS) and polyethylene (PE) were major polymer types in the samples. The distribution of MPs in the study area reflected a patchy and irregular spatial pattern implying that the higher MPs concentration are near mouth of permanent rivers and in the regions with higher level of the fishing and tourism activities. The results showed the wide occurrence of MPs in the sediments of the world's largest lake which extend the knowledge on MPs pollution in the marine system. We also recommend further research on microplastics in different compartments of Caspian Sea to inform policy discussions and the development of appropriate management responses. Graphical abstract: Image 1 Highlights: Microplastics abundance were studied for the first time in the Caspian Sea. Microplastic levels were comparable with those found in worldwide marine sediments. Polystyrene and Polyethylene were the main polymer types. Fishing and tourism might be the main sources of MPs in the coasts.